MODELS AND TECHNIQUES IN GEODETIC MONITORING OF TECTONIC DEFORMATIONS IN GREECE - Rossikopoulos, D.; Fotiou, A.; Pikridas, C.; Bitharis, S. (Bulletin of the Geological Society of Greece, 2016)
The assessment and interpretation of the geodetic results regarding the detection of possible spatial displacements and the deformation parameters have to be combined with a realistic geophysical model for the area. Usually, this study is carried out by fitting the geodetic data to a polynomial function, which is considered sufficient to describe adequately the deformation pattern. In terms of the computational steps needed, this polynomial fitting can be accomplished simultaneously by the analysis of the geodetic observations in a dynamic adjustment or non simultaneously in a sequential approach. The main goal of this article is to give a short description of the related methods and to present rigorous processing strategies for the analysis of GNSS observations from continuously permanent stations in order to create a modern and improved geodetic velocity field for Greece. Emphasis is given on the reference frame definition problem.